Effectiveness of SB5, an Adalimumab Biosimilar, in Patients With Noninfectious Uveitis: A Real-Life Monocentric Experience. Issue 4 (July 2021) - Sota, Jurgen; Gentileschi, Stefano; Vitale, Antonio; Gaggiano, Carla; De Bartolo, Giuseppe; Bianco, Maria Teresa; Frediani, Bruno; Tosi, Gian Marco; Cantarini, Luca; Fabiani, Claudia
Abstract : Purpose: Several concerns have arisen with biosimilars in terms of immunogenicity, safety issues, loss of efficacy, and extrapolation to other indications. The study aim was to evaluate the efficacy of SB5, an adalimumab biosimilar, in noninfectious uveitis (NIU). Design: Retrospective nonrandomized study. Methods: Data from patients with refractory NIU treated with SB5 (Imraldi, Biogen) were analyzed at baseline, 3 months after SB5 initiation and at the last follow-up in terms of uveitis relapses, occurrence of retinal vasculitis, resolution of uveitic macular edema (UME), best-corrected visual acuity, glucocorticoids (GCs)-sparing effect and drug survival. Results: Uveitis relapses decreased from 121 relapses/100 patients/year in the 12 months before SB5 initiation to 4 relapses/100 patients/year during the first 12 months of treatment ( P  = 0.0004). Uveitis was inactive in 46/47 eyes at the end of the study period. The number of eyes with active retinal vasculitis decreased during the study period ( P  < 0.0001). At baseline, 6 eyes presented UME, whereas no eye had UME at the last follow-up. Mean best-corrected visual acuity increased from 7.7 ± 3.41 at baseline to 8.9 ± 2.46 at the last follow-up ( P  = 0.0045). Mean GCs daily dosage decreased from 18.33 ± 10.33 mg at baseline to 5.75 ± 2.29 mg at the last follow-up ( P  = 0.018). The cumulative SB5 retention rate was 91.8% at both 12- and 20-month follow-up. Conclusions: SB5 biosimilar is effective in NIU by drastically reducing uveitis relapses and the occurrence of retinal vasculitis. Moreover, SB5 biosimilar improved visual acuity, allowed a significant GCs-sparing effect and showed an excellent drug retention rate.